Accreting transition discs with large cavities created by X-ray photoevaporation in C and O depleted discs. (13th October 2017) - Ercolano, Barbara; Weber, Michael L.; Owen, James E.
Abstract: Circumstellar discs with large dust depleted cavities and vigorous accretion on to the central star are often considered signposts for (multiple) giant planet formation. In this Letter, we show that X-ray photoevaporation operating in discs with modest (factors 3–10) gas-phase depletion of carbon and oxygen at large radii ( > 15 au) yields the inner radius and accretion rates for most of the observed discs, without the need to invoke giant planet formation. We present one-dimensional viscous evolution models of discs affected by X-ray photoevaporation assuming moderate gas-phase depletion of carbon and oxygen, well within the range reported by recent observations. Our models use a simplified prescription for scaling the X-ray photoevaporation rates and profiles at different metallicity, and our quantitative result depends on this scaling. While more rigorous hydrodynamical modelling of mass-loss profiles at low metallicities is required to constrain the observational parameter space that can be explained by our models, the general conclusion that metal sequestering at large radii may be responsible for the observed diversity of transition discs is shown to be robust. Gap opening by giant planet formation may still be responsible for a number of observed transition discs with large cavities and very high accretion rate.